(untitled) (Geography and Tourism, 2022)
The tourism sector is responsible for a large part of Greece's GDP because the tourist assets of this country generate a lot of tourist traffic. The aim of the article is to compare the tourist attractiveness of the Ionian Islands, Dodecanese and Crete. This allowed for the creation of an attractiveness index. The following aspects were analyzed in detail: the number of tourist attractions, the number of hotels, the quality of these hotels, the number of airports and the number of seaports. Each of the elements was rated on a five-point scale. The region of the Ionian Islands turned out to be the most attractive for tourists. It has the most seaports and airports, so it is the most available in terms of communication. The number of attractions in the Ionian Islands is the largest among the studied areas. The number and quality of hotels is comparable to other analyzed places.